The Hare has lost his Spectacles. Notes on Contest Scenes, Early Occurrences - Dittmann, Reinhard (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
The Contest Scene is beyond doubt the most popular motif of the Early Dynastic glyptic. In this short contribution I will focus exclusively on material from the Diyala sites, excavated by Frankfort and his team as well as on the SIS-material from Ur.